Purin-6-One Derivatives as Phosphodiesterase-2 Inhibitors - Wei Yuan; Xin-Yun Zhao; Xi Chen; Chang-Guo Zhan (Journal of Chemistry)
A series of purin-6-one derivatives were synthesized, and their in vitro inhibitory activity against phosphodiesterase-2 (PDE2) was evaluated by using a fluorescence polarization assay. Three compounds, that are, 2j, 2p, and 2q, showed significant inhibitory activity against PDE2 with IC50 values of 1.73, 0.18, and 3.43 μM, respectively. Structure-activity relationship (SAR) analysis was performed to explore the relationship between the chemical structures of these compounds and their inhibitory activity. Compounds 2j, 2p, and 2q were further selected for molecular docking study. The docking results suggested that these ligands bind with hydrophobic pockets of the catalytic active site of PDE2, where a Tyr655 residue was found to be important in binding with compound 2p, the most potent inhibitor identified in this study. Our present study provides useful information for the future design of novel PDE2 inhibitors.